Relationships between Behavioural Addictions and Psychiatric Disorders: What Is Known and What Is Yet to Be Learned? - Starcevic, Vladan; Khazaal, Yasser (Frontiers in Psychiatry, 2017)
This article provides a narrative review of the relationships between several behavioural addictions (pathological gambling, problematic Internet use, problematic online gaming, compulsive sexual behaviour disorder, compulsive buying and exercise addiction) and psychiatric disorders. Associations between most behavioural addictions and depressive and anxiety disorders are strong and seem relatively nonspecific. Strong links with substance use disorders may support the notion that some people are more prone to addictive behaviours, regardless of whether these involve substances or problematic activities. Other associations seem relatively specific, for example, those between problematic Internet use/online gaming and attention deficit/hyperactivity disorder, between compulsive buying on one hand and eating disorders and hoarding on the other and between exercise addiction and eating disorders. The quality of the research varies, but most studies suffer from methodological limitations, including a cross-sectional or correlational design, non-representative study populations, small sample sizes, reliance on self-report assessment instruments, diverse diagnostic criteria and conceptual heterogeneity of most behavioural addictions. Due to these limitations, generalizability of the findings is questionable and the direction of causality, if any, is unknown in the relationships between behavioural addictions and psychiatric disorders. Regardless of the aetiological uncertainty, these relationships often call for a modified treatment approach. Prospective studies are needed to clarify the longitudinal relationships between behavioural addictions and psychiatric disorders.